Persepsi Mahasiswa Generasi Z Terhadap Stres Akademik Di Era Digital: Studi Fenomenologis Pada Pendidikan Vokasi - I Kadek Andre Dwika Permana Putra; Mohammad Akbar Firizki; Ruth Vina Avrilia Sinaga; Imam Alfarizi Siregar (Universitas Muhammadiyah Gresik, 2026)
Background: Generation Z, as digital natives, brings unique characteristics to the learning process, including a preference for fast, practical, and relevant learning. In vocational education, which is required to adapt to industry needs in the digital era, a mismatch between student expectations and the reality of learning can trigger academic stress. Objective: This study aims to explore the forms of academic stressors, understand the meaning of stressful experiences, and identify the influence of technology and digital media on academic stress among Generation Z vocational students. Method: Using a qualitative approach with a phenomenological design, this study involved seven vocational students from various disciplines through in-depth interviews. Results: Results indicate that academic stress is influenced by high task demands, an imbalance between theory and practice, and obstacles to online learning such as technical glitches and internet dependence. Social media exacerbates stress through social comparison and pressure to perform productively, although it still provides social support. Students also reported a decreased sense of control in the digital ecosystem, although some are able to adapt through independent time management. Conclusion: These findings emphasize the need for responsive vocational education policies, improved digital platform quality, academic flexibility, and counseling services to support student mental well-being.